PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TRANSKOM INTEGRASI MANDIRI KOTA TANGERANG SELATAN - Ine Rahmawati Alawiyah; Rahmayanti Tumanggor (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine whether the work environment and work discipline, both partially and simultaneously, have a positive and significant influence on employee performance at PT Transkomintegration Mandiri, South Tangerang City. This research uses an associative quantitative research method where the data obtained is in the form of a questionnaire which is processed using the SPSS 2.5 application. The results show the influence of the work environment on employee performance at PT Transkomintegra Mandiri, South Tangerang City. Shown by the regression equation Y = 17.562 + 0.573 The calculated t value of the Work Environment is 3.616 which is greater than the t table value of 1.66600 with a significance level of 0.001 which is smaller than 0.05, so it can be interpreted that H1 is accepted and H0 is rejected, so it can be partially concluded that the Work Environment has a positive and significant effect on employee performance, There is an influence of work discipline on employee performance at PT Transkomintegration Mandiri, South Tangerang City, shown by the regression equation Y = 19.169 + 0.529X2, the correlation coefficient (R) value is 0.555, which means the coefficient between variables X2 to Y is moderate. The tcount value of the Work Discipline variable is 2.665 which is greater than the ttable of 1.66600 with a significance level of 0.009 which is smaller than 0.05, so it can be interpreted that H2 is accepted and H0 is rejected. So it can be partially concluded that Work Discipline has a positive and significant effect on Employee Performance, There is an influence of the work environment and work discipline on employee performance at PT Transkomintegration Mandiri, South Tangerang City. Proven by the regression equation Y = 12.959 + 0.395 % obtained from Adjust R Square, namely KD = 0.398 x 100% = 39.8% while the remaining 60.2% (100% - 39.8%) is the influence of other factors that were not studied. The output is known to be Fcount of 25.459 and the significance value is 0 while the value is 3.12. So it can be concluded that Fcount > Ftable (25.459 > 3.12) and significance < 0.05 (0.000 < 0.05), then H3 is accepted, so it can be concluded that there is a positive and significant influence simultaneously between environmental variables work and work discipline on employee performance.